Rethinking Judicial Modernity and Normative Pluralism: A Critical Review on the Transformation of Sharia in Saudi Arabia (A Review of Islamic Law in Saudi Arabia) - M. Holil; Ishaq Ishaq; Muhammad Fauzinuddin Faiz (UIN Sunan Kalijaga Yogyakarta, 2026)
The relationship between traditional Islamic law and government-driven legal reform is one of the most vital topics in contemporary legal studies. In modern Muslim majority countries, especially Saudi Arabia, the shift from unregulated judicial discretion to formal codification poses a significant challenge to established religious authority and judicial independence. This article critically analyzes the theoretical and practical consequences of rendering Sharia more positive through the principles of siyasa sharʿiyya and salafi legal approach. This study examines the dynamics of normative pluralism in state run court systems, emphasizing the conflicts among judicial ijtihad, executive centralization, and international human rights influences. In the end, examining this legal change is crucial for grasping how Sharia adapts within contemporary governmental frameworks without simply descending into secularization or authoritarian legalism. Interaksi antara yurisprudensi islam klasik dan reformasi hukum yang diprakarsai negara merupakan salah satu isu paling krusial dalam studi hukum modern. Di negara-negara berpenduduk mayoritas muslim kontemporer, khususnya Arab Saudi, transisi dari diskresi yudisial yang tidak terstandarisasi menuju kodifikasi terstruktur menghadirkan tantangan mendasar bagi otoritas keagamaan tradisional dan otonomi peradilan. Artikel ini secara kritis menguji implikasi teoretis dan praktis dari positivisasi syariah melalui doktrin siyasa sharʿiyya dan metodologi hukum salafi. Dengan mengevaluasi dinamika